Ecomorphological adaptations of owl feet and talons. (11th January 2023) - Cameron, C.; Johnson, D. H.; Gauthier, G.; Lecomte, N.; Therrien, J.‐F.
Abstract: Feet and talons are the most specialized predatory attributes of raptor morphology. As such, the hindlimb morphology of owls should reflect their dietary specialization. Owls' diet varies widely between species with only a subset of owl species preying predominantly on small mammals. We hypothesize that different owl species have varied hindlimb morphology, adapted to their main prey types, and that only dietary specialists will be distinguishable based on talon morphology (e.g. toe length, talon curvature and thickness, etc.). We used a sample of 63 specimens from 15 owl species to obtain a variety of measurements of hindlimb morphology. We then used a discriminant function analysis to investigate the degree of variation between species and diet groups in terms of their morphological measurements. Our results indicate that talon morphology is linked to prey type in the owl species studied. Insect specialists and small mammal specialists were characterized by a low talon curvature, whereas generalists presented a pronounced talon curvature. Fish specialists presented particularly thick and robust talons, and insect specialists showed lower digit strength than other owl species. These findings could help determine the diet of other owl species, particularly endangered species for which data on diet is often scarce. This study will also be very useful in future studies of the ecology of sympatric species, resource partitioning between species, or between sexes of the same species, and more generally to the evolution of owls. Abstract : Talon morphology is linked to prey type in owl species. Insect specialists and small mammal specialists are characterized by a low talon curvature, whereas generalists and seasonal small mammal specialists present a pronounced talon curvature. Fish specialists present particularly thick and robust talons, and insect specialists show lower digit strength than any other owl species.